Exploring Childbirth Experiences among Adolescent in Imenti South Sub County - MANENE, JACQUELINE GATABI; Kaimuri, Dr. MaryJoy (Meru Universty of Science and Technology International Conference (MUSTIC), 2025)
Introduction: Adolescent childbirth experience is the aspect of giving birth as perceived and experienced by the adolescent from pregnancy, delivery to postpartum period including physical, emotional and social dimensions. Adolescent childbirth is a global health issues, 21 million girls aged between 10-19 years giving birth yearly. Adolescent childbirth is associated with higher risk of maternal and infant mortality among ages 10-19 years globally and complications during pregnancy and child birth are the second cause of death to the same population. The objective of the study is to examine childbirth experiences among adolescents seeking services in Imenti South Sub County of Meru County. Methods: A qualitative descriptive design, will be used to conduct this study in Imenti South Sub County. The study population will be adolescent mothers who have been attended in the public level four hospitals seeking antenatal and postnatal care in Imenti South Sub County. A sample size of 100 adolescent mothers will participate in the study. In-depth interviews and thematic analysis will be used to capture challenges experienced by adolescents during childbirth. A list of participants will be generated from the hospital records in the targeted study location using purposive sampling technique. The identified participants will be traced from the MOH 333 register and reached via telephone call. Focused groups discussion will be used to collect information from the participants. Data collected will be analyzed using NVivo software to organize code and analyze qualitative data. Research findings will be presented in thematic analysis. All ethical consideration will be adhered to by informing the selected participants the purpose of the study, seeking ethical clearance from Meru University of Science and Technology (MUST) Institutional Research Ethics Review Committee MIRERC and the necessary permit obtained from National Commission of Science and Technology and Innovation (NACOSTI). Informed consent will be sought from the study participants through their guardians and parents.